Experimental Investigation on Fracture Properties of HTPB Propellant with Circumferentially Notched Cylinder Sample. Issue 7 (27th May 2022) - Wang, Zhejun; Qiang, Hongfu; Wang, Jiaxiang; Duan, Leiguang
Abstract: To comprehensively understand the fracture properties of solid propellants, the mode I tensile fracture toughness tests at different temperatures (253.15–343.15 K) and loading rates (2–500 mm/min) were conducted on the newly designed circumferentially notched cylinder sample with different initial crack sizes (4.5 and 6.5 mm) for hydroxyl‐terminated polybutadiene (HTPB) propellant. Test results reveal that the shape of the tensile fracture stress‐strain curves was not significantly influenced by temperature, loading rate and the initial crack size. Higher loading rate and lower temperature can lead to a rise in the tensile fracture toughness of HTPB propellant described by the stress intensity factor, however, continuously increasing loading rate cannot dramatically improve this fracture toughness beyond the rate of 250 mm/min. In addition, the fracture toughness is more sensitive to temperature. Furthermore, the variation of the initial crack size causes obvious changes in the fracture toughness with the coupled effects of low temperature and higher loading rates. At these test conditions, a higher tensile fracture toughness can be obtained with the shorter initial crack. For all the test conditions, there is a linear rise in the strain corresponding to the fracture toughness as temperature increases. Meanwhile, this strain increases with the shorter initial crack. Whereas, the effect of loading rate on this strain is complex. Based on the time‐temperature superposition principle (TTSP), the master curves with a log‐curvilinear form were constructed to predict the mode I tensile fracture toughness of the propellant at different initial crack sizes in a wide range of loading conditions. Abstract :